Pengembangan Aplikasi Taskify Untuk Manajemen Tugas Menggunakan Framework Laravel - Zamzami, Muhammad Aryaka; Kurnia Kito, Ramadani; Suratno, Igo Prayoga; Maritza, Kaka Irsyad; Salamah, Umniy (JSAI (Journal Scientific and Applied Informatics), 2024)
Task management is one of the important aspects that support success in learning and working activities. The number of tasks and responsibilities often creates challenges, such as forgetting schedules or errors in recording tasks manually. To overcome these problems, a technology-based solution is needed, one of which is a web-based task management application that can help users organize and monitor tasks in a more structured manner. This research adopts a software development approach based on the Agile method, which allows the process of iteration and development that is adaptive to user needs. The “Taskify” application was developed using the Laravel framework to support backend functionality and MySQL as a database. Application testing is carried out using the Blackbox Testing method to ensure all features run according to user needs. The app also features a user-friendly and responsive interface, providing an optimal user experience..